Clinical Outcomes Among Working Adults Using the Health Integrator Smartphone App: Analyses of Prespecified Secondary Outcomes in a Randomized Controlled Trial - Stephanie Bonn; Gabriella Licitra; Rino Bellocco; Ylva Trolle Lagerros (JMIR Publications, 2022)
BackgroundThere is a need to find new methods that can enhance the individuals' engagement in self-care and increase compliance to a healthy lifestyle for the prevention of noncommunicable diseases and improved quality of life. Mobile health (mHealth) apps could provide large-scale, cost-efficient digital solutions to implement lifestyle change, which as a corollary may enhance quality of life. ObjectiveHere we evaluate if the use of a smartphone-based self-management system, the Health Integrator app, with or without telephone counseling by a health coach, had an effect on clinical variables (secondary outcomes) of importance for noncommunicable diseases. MethodsThe study was a 3-armed parallel randomized controlled trial. Participants were randomized to a control group or to 1 of 2 intervention groups using the Health Integrator app with or without additional telephone counseling for 3 months. Clinical variables were assessed before the start of the intervention (baseline) and after 3 months. Due to the nature of the intervention, targeting lifestyle changes, participants were not blinded to their allocation. Robust linear regression with complete case analysis was performed to study the intervention effect among the intervention groups, both in the entire sample and stratifying by type of work (office worker vs bus driver) and sex. ResultsComplete data at baseline and follow-up were obtained from 205 and 191 participants, respectively. The mean age of participants was 48.3 (SD 10) years; 61.5% (126/205) were men and 52.2% (107/205) were bus drivers. Improvements were observed at follow-up among participants in the intervention arms. There was a small statistically significant effect on waist circumference (β=-0.97, 95% CI -1.84 to -0.10) in the group receiving the app and additional coach support compared to the control group, but no other statistically significant differences were seen. However, participants receiving only the app had statistically significantly lower BMI (β=-0.35, 95% CI -0.61 to -0.09), body weight (β=-1.08, 95% CI -1.92 to -0.26), waist circumference (β=-1.35, 95% CI -2.24 to -0.45), and body fat percentage (β=-0.83, 95% CI -1.65 to -0.02) at follow-up compared to the controls. There was a statistically significant difference in systolic blood pressure between the two intervention groups at follow-up (β=-3.74, 95% CI -7.32 to -0.16); no other statistically significant differences in outcome variables were seen. ConclusionsParticipants randomized to use the Health Integrator smartphone app showed small but statistically significant differences in body weight, BMI, waist circumference, and body fat percentage compared to controls after a 3-month intervention. The effect of additional coaching together with use of the app is unclear. Trial RegistrationClinicalTrials.gov NCT03579342; https://clinicaltrials.gov/ct2/show/NCT03579342 International Registered Report Identifier (IRRID)RR2-10.1186/s12889-019-6595-6